Duck gasdermin E is a substrate of caspase-3/-7 and an executioner of pyroptosis - Li, Hanqing; Wang, Xin; Yu, Lanjie; Wang, Junwei; Cao, Yongsheng; Ma, Bo; Zhang, Wenlong (Frontiers in Immunology, 2023)
Gasdermin (GSDM)-mediated cell death is an ancient immune defensive mechanism that plays an essential role in bacteria, fungi, coral, teleost, and mammals. After being cleaved by proteases of hosts or pathogens, amino-terminal (NT) fragment of GSDMs (GSDM-NTs) form pores in the membrane structure of cells, thereby leading to pyroptotic cell death. However, the expression profile, activation mechanism and function of avian GSDMs have not been studied in depth yet. In the current study, genes encoding duck gasdermin E (duGSDME), caspase-3 (ducaspase-3) and ducaspase-7 were cloned from mRNA of a virus-challenged duck embryo. The cleavage of duGSDME by ducaspase-3/-7 was verified in the cell-free system and/or in human embryonic kidney cells (HEK293). Ducaspase-3/-7 could recognize and cleave duGSDME at 270DAVD273. Overexpression of duGSDME-NT (1-273aa) fragment led to pyroptosis-like morphological change, increased lactic dehydrogenase (LDH) release and propidium iodide uptake of HEK293 cells, which indicated that duGSDME-NTs could cause cell membrane damage. In addition, recombinantly expressed duGSDME-NT showed bactericidal activity to an enterotoxic Escherichia coli (F5+) strain. The expression level of duGSDME was low in duckling tissues. DHAV-3 challenge upregulated the expression of duGSDME and ducaspase-3 in different tissues and led to the activation of ducaspase-3 and cleavage of duGSDME. The results indicated that duGSDME is a substrate of ducapsase-3/-7, and duGSDME-NT can cause pyroptosis. In addition, duGSDME may play a role in the immune defense of ducks against infectious diseases after being cleaved by ducaspase-3. The current study provides essential information for further investigation of the mechanisms of avian innate immunity and avian diseases.